The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fcimb.2017.00541
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Induced HB-EGF Upregulates Gastrin Expression via the EGF Receptor, C-Raf, Mek1, and Erk2 in the MAPK Pathway

Abstract: Helicobacter pylori is associated with hypergastrinemia, which has been linked to the development of gastric diseases. Although the molecular mechanism is not fully understood, H. pylori is known to modulate the Erk pathway for induction of gastrin expression. Herein we found that an epidermal growth factor (EGF) receptor kinase inhibitor significantly blocked H. pylori-induced gastrin promoter activity, suggesting involvement of EGF receptor ligands. Indeed, H. pylori induced mRNA expression of EGF family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…In another study, levels of EGF, EGFR and a homolog of EGFR (c-erb-B2) were shown to be elevated in gastric mucosa of patients suffering from chronic gastritis with a Helicobacter pylori infection, and were comparable to samples from gastric cancer patients [28]. Subsequent work showed that H. pylori possessing an intact T4SS induced gastrin promoter activity through HB-EGF and EGFR [29]. In turn, gastrin could affect a variety of epithelial cell activities, including proliferation [30].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 94%
“…In another study, levels of EGF, EGFR and a homolog of EGFR (c-erb-B2) were shown to be elevated in gastric mucosa of patients suffering from chronic gastritis with a Helicobacter pylori infection, and were comparable to samples from gastric cancer patients [28]. Subsequent work showed that H. pylori possessing an intact T4SS induced gastrin promoter activity through HB-EGF and EGFR [29]. In turn, gastrin could affect a variety of epithelial cell activities, including proliferation [30].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 94%
“…MMP-7 and HB-EGF expression is upregulated by H. pylori infection and is associated with EMT [274,275]. Likewise, MMP-7 overexpression is because of increased levels of gastrin, activator protein 1 (AP-1), and NF-kB induced by H. pylori infection [276][277][278][279]. Levels of MMP-7 might correlate with the degree of rehabilitation after treatment and poor prognosis in gastric cancer survival [270,280].…”
Section: Heparin-binding Epidermal Growth Factor and Matrix Metalloprmentioning
confidence: 99%
“…Hence, transgenic mice overexpressing gastrin under the transcriptional control of the insulin promoter (INS‐GAS mice) rapidly develop gastric malignancies after H. pylori infection . Gunawardhana et al found that the induction of the gene encoding gastrin by H. pylori is abolished in the presence of AG1478, an inhibitor of epidermal growth factor receptor (EGFR) in AGS cells . Using siRNAs to specifically knockdown various signaling molecules, these authors demonstrated that H. pylori first induces the release of heparin‐binding epidermal growth factor‐like growth factor (HB‐EGF), which in turn signals via Raf‐1 proto‐oncogene, serine/threonine kinase (RAF1), mitogen‐activated protein kinase kinase 1 (MAP2K1, previously known as MEK1), and mitogen‐activated protein kinase 1 (MAPK1, also called ERK2) to stimulate the transcription of the gene encoding gastrin .…”
Section: Inflammationmentioning
confidence: 99%
“…Gunawardhana et al found that the induction of the gene encoding gastrin by H. pylori is abolished in the presence of AG1478, an inhibitor of epidermal growth factor receptor (EGFR) in AGS cells . Using siRNAs to specifically knockdown various signaling molecules, these authors demonstrated that H. pylori first induces the release of heparin‐binding epidermal growth factor‐like growth factor (HB‐EGF), which in turn signals via Raf‐1 proto‐oncogene, serine/threonine kinase (RAF1), mitogen‐activated protein kinase kinase 1 (MAP2K1, previously known as MEK1), and mitogen‐activated protein kinase 1 (MAPK1, also called ERK2) to stimulate the transcription of the gene encoding gastrin . In the same way, it has been already reported that there is increased EGFR phosphorylation in the H. pylori ‐induced human gastric inflammation and cancer development .…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation